1988
DOI: 10.1111/j.1476-5381.1988.tb11624.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the origin of the high pressure neurological syndrome: the interaction between pressure, strychnine and 1,2‐propandiols in the mouse

Abstract: 1 The effects of a variety of structural isomers of the centrally acting muscle relaxant mephenesin on the high pressure neurological syndrome have been investigated. Threshold pressures for the onset of the behavioural signs, tremors and convulsions, were established. The effects of these compounds on the response to pressure were also compared with their ability to antagonize the convulsive action of strychnine. 2 The dose-response relationships for strychnine and picrotoxin were investigated at fixed pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
1
12
1
Order By: Relevance
“…The initial observation that the effect of strychnine was strictly additive with pressure led to the theory that increased hydrostatic pressure might have some effect on inhibitory glycinergic transmission (Bowser-Riley et al, 1988). However, the present experiments suggest that some of these drugs might instead act at the excitatory SI-glycine site associated with the NMDA receptor.…”
Section: Mechanism Of Effect Ofpressurecontrasting
confidence: 49%
See 2 more Smart Citations
“…The initial observation that the effect of strychnine was strictly additive with pressure led to the theory that increased hydrostatic pressure might have some effect on inhibitory glycinergic transmission (Bowser-Riley et al, 1988). However, the present experiments suggest that some of these drugs might instead act at the excitatory SI-glycine site associated with the NMDA receptor.…”
Section: Mechanism Of Effect Ofpressurecontrasting
confidence: 49%
“…Both these hypotheses predict that NMDA antagonists would be effective against HPNS, and indeed they are (Meldrum et al, 1983;Milan et al, 1990). However, the facts that bicuculline (Bowser-Riley et al, 1989a) and picrotoxin (Bowser-Riley et al, 1988) do not act additively with pressure, and that pressure selectively inhibits currents evoked by glycine (as opposed to GABA or kainate (Daniels et al, 1993)), both favour the second hypothesis; that pressure reduces glycinergic inhibition and hence indirectly regulates the NMDA gated channel.…”
Section: Mechanism Of Effect Ofpressurementioning
confidence: 99%
See 1 more Smart Citation
“…These effects not only represent a serious threat to the safety of divers presently operating at pressures up to 45 bar but also provide a barrier to deeper human diving. propan-1,2-diol), a centrally acting muscle relaxant, has been shown to be a most potent anti-HPNS drug in mice: it raised the onset pressure for tremors by a factor of 2.5 and that for convulsions by a factor of 1.5 (Bowser-Riley, 1984;Bowser-Riley et al, 1988). Experiments with simple structural isomers of mephenesin also suggested a possible mechanism for the convulsive action of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…properties against strychnine, picrotoxin and metrazol (Bowser-Riley, 1984), with the aromatic propandiols being effective only against strychnine and ineffective against metrazol or picrotoxin and the reverse being the case for the aliphatic compounds. In addition, it was shown that the ortho, meta and para isomers of mephensin and the ortho and para isomers of chlorphenesin (3[2-chlorphenoxy]propan-1,2-diol) exhibited an identical order of potency against both the convulsive action of pressure and that of strychnine (Bowser-Riley et al, 1988). The apparent link between the action of pressure and strychnine and their mutual antagonism by mephenesin was strengthened by the finding that strychnine and pressure act in a strictly additive manner in the production of convulsions and that this relationship was maintained in the presence of mephenesin (Bowser-Riley et al, 1988).…”
Section: Introductionmentioning
confidence: 99%